PENGGUNAAN TEKNIK MODELING UNTUK MENINGKATKAN KECERDASAN EMOSI SISWA TUNALARAS KELAS VII LPKA SUKAMISKIN - Rahman, Agus Saepul (2017)
The problem faced by the tunalaras students of class VII in LPKA Sukamiskin low level of emotional intelligence as a result of environmental factors such as the association of peers. Emotional intelligence of low students with emotional and behavior disorder includes skills in recognizing emotions, managing emotions, motivating himself, empathy and fostering relationships with others. This study aims to determine the effect of using modeling techniques to improve the emotional intelligence of grade VII students tunalaras of LPKA Sukamiskin. The method used in this research is the experimental method with Pre-experimental one group Pre-test Post-test design. Data processing using Wilcoxon signed rank test with SPSS. Place of research in LPKA Sukamiskin Bandung with the number of samples are 16 students. Sampling technique using random sampling. The results showed that the use of modeling techniques can improve students emotional intelligence tunalaras evidenced by Wilcoxon Signed Rank Test results on SPSS showed the value of p Value obtained from the calculation is smaller than the critical value (0.001<0.05). Researchers recommend modeling techniques can be used as an effort to improve emotional intelligence.---------- Permasalahan yang dihadapi siswa tunalaras kelas VII di LPKA Sukamiskin yaitu rendahnya kecerdasan emosi yang diakibatkan dari faktor lingkungan seperti pergaulan dari rekan sebaya. Kecerdasan emosi siswa tunalaras yang rendah meliputi keterampilan dalam mengenal emosi, mengelola emosi, memotivasi diri, empati dan membina hubungan dengan orang lain. Penelitian ini bertujuan mengetahui pengaruh penggunaan teknik modeling untuk meningkatkan kecerdasan emosi siswa tunalaras kelas VII LPKA Sukamiskin. Metode yang digunakan dalam penelitian adalah metode eksperimen dengan desain Pre-experimental one group Pre-test Post-test. Pengolahan data menggunakan uji perbandingan Wilcoxon signed rank test dengan SPSS. Tempat penelitian di LPKA Sukamiskin Bandung dengan jumlah sampel sebanyak 16 siswa. Teknik pengambilan sampel menggunakan random sampling. Hasil penelitian menunjukan penggunaan teknik modeling dapat meningkatkan kecerdasan emosi siswa tunalaras yang dibuktikan dengan hasil uji Wilcoxon Signed Rank Test pada SPSS menunjukan nilai p Value yang diperoleh dari hasil perhitungan lebih kecil dari nilai kritis (0,001 < 0,05). Peneliti merekomendasikan teknik modeling dapat digunakan sebagai salah satu upaya untuk meningkatkan kecerdasan emosi